ПРОФЕСІЙНІ ЗДОБУТКИ УКРАЇНСЬКОЇ ДІАСПОРИ У ТВОРЕННІ НАЦІОНАЛЬНОЇ ТЕРМІНОЛОГІЇ - Джус О. В. (World Science, 2019)
The article analyzes the professional achievements of the Ukrainian diaspora in the creation of national terminology. Recognizing the importance of responsibility, based on national principles of terminology and lexicography, scholars of the Ukrainian diaspora actively work on the creation of new textbooks and terminology dictionaries in various fields of knowledge with wide use of Ukrainian phraseology. Based on the primary sources, periodicals of the states of the potential settlement of the Ukrainian immigrants, the memoirs and scientific explorations of scientists of Ukraine, Ukrainian abroad, the unfolding of the Ukrainian lexicographic tradition in the Ukrainian diaspora has been traced. Emphasis is placed on the implementation of the European experience in the professional training of future specialists and the improvement of professional skills of specialists. The educational and educational context of the functioning of the Ukrainian diaspora, in particular the publication of professional reference literature, the popularization of scientific knowledge in the environment of Ukrainian emigration as a component of the resistance to Russification policy in the USSR. The important aspect of using their stay in emigration by Ukrainians as an opportunity to advance Ukrainian national interests was emphasized. The role of prominent representatives of the Ukrainian diaspora in spreading and preserving the Ukrainian language and national culture has been clarified.